Problematika Pembelajaran Online Mahasiswa Program Studi Pendidikan Bahasa Jerman - Kalvin Karuna (Universitas Pattimura, 2021)
Before the Covid 19 pandemic, online learning was not the first choice for lecturers and teachers in presenting their teaching materials. Therefore, its use during a pandemic represents a sudden change that can cause problems. The purpose of this study is to describe the problems faced by students in the German as a Foreign Language program, FKIP UNPATTI, related to the use of online learning during the Covid 19 pandemic. This was a descriptive research method involving 25 active students. The results of the analysis showed that 21 (84%) of total 25 students participated in online lectures by using the Internet on campus, but were not satisfied because of the weak Internet network, so they had to prepare their own data packages, while 20 (80%) of the total students admitted that online learning was a new experience for them, even though 23 (92%) wanted normal lectures as they had done before. Thus, there are two major issues identified in this study, namely the availability of support facilities for online learning and the mental readiness of students to face the changes in learning culture